2018
DOI: 10.3390/jmse6030074
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Grass Covered Flood Defences with Roads on Top Due to Wave Overtopping: A Probabilistic Assessment Method

Abstract: Abstract:Hard structures, i.e., roads, are commonly found over flood defences, such as dikes, in order to ensure access and connectivity between flood protected areas. Several climate change future scenario studies have concluded that flood defences will be required to withstand more severe storms than the ones used for their original design. Therefore, this paper presents a probabilistic methodology to assess the effect of a road on top of a dike: it gives the failure probability of the grass cover due to wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 32 publications
3
46
2
Order By: Relevance
“…Transitions in cover type affect both the hydraulic load on the cover and the strength of the cover. The change in bed roughness increases the hydraulic load by creating extra turbulence (Bomers et al, 2018). In case of transitions from grass to another cover type, the strength of the grass cover is reduced because the grass cover is unattached on one side.…”
Section: Transitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Transitions in cover type affect both the hydraulic load on the cover and the strength of the cover. The change in bed roughness increases the hydraulic load by creating extra turbulence (Bomers et al, 2018). In case of transitions from grass to another cover type, the strength of the grass cover is reduced because the grass cover is unattached on one side.…”
Section: Transitionsmentioning
confidence: 99%
“…Experiments and numerical models have shown that transitions are weak spots along the dike (Steendam, 2014;Bomers et al 2018;Aguilar-López et al 2018). The increase in the hydraulic load and the reducing cover strength makes transitions vulnerable for dike cover erosion.…”
Section: Research Gap and Planmentioning
confidence: 99%
See 3 more Smart Citations